COVID-19 lockdown: the unspoken toll on the 65+ community in Turkey. Issue 4 (18th November 2020) - Ates, Ozgur
Abstract : Purpose: On March 21, 2020, the Turkish Government imposed a curfew for citizens 65 years old and over and ordered them to stay at home as a measure to protect them against the COVID-19 outbreak. The curfew ended on June 10, 2020, having lasted 82 days. The purpose of this paper is to examine the significant emotional burden on the elderly, as they felt excluded and battled with despair during the lockdown. Design/methodology/approach: This reflective paper shares the COVID-19 lockdown experiences of the author with a group of elderly residents of a small community in Ankara, Turkey. Through semi-structured interviews and analysis, three overarching themes of the residents' experience were identified: vulnerability, social isolation/loneliness and ageism. Findings: The elderly in the community are individuals who get their social interaction outside the home. As a result of the nearly three months of social isolation, they have experienced social disconnection and health problems, Originality/value: To the best of the author's knowledge, this is the first attempt to give voice to the silenced group of elderly and share their thoughts and feelings during this difficult COVID-19 lockdown in Turkey.